The effect of ownership structure to the firm performance in Malaysia / Sinnah Mad - Mad, Sinnah (2014)
This study is to identify the relationship between the ownership structures and the firm performance in Malaysia by using the simple linear regression. There have four types of ownership structure which are family ownership, government ownership, managerial ownership and institutional ownership. Dividend per share(DPS) as a proxy for the ownership structure and Return on assets(ROA) and return on equity(ROE) will measure the firm performance of the company. From the result, family, managerial and institutional ownership have a relationship between the DPS and ROA, while for the DPS and ROE, all of ownership have relationship between to variable.